2021
DOI: 10.1007/s10493-021-00597-4
|View full text |Cite
|
Sign up to set email alerts
|

Oribatid mite communities in mountain scree: stable isotopes (15N, 13C) reveal three trophic levels of exclusively sexual species

Abstract: Mountain scree habitats are intermediate habitats between the base of the soil and the bedrock. They are composed of a network of small cracks and voids, and are commonly situated at the lower levels of scree slopes. Their environment is defined by empty spaces inside the scree, the absence of light and photoperiod, low temperature, and resource poor conditions. Soil arthropod communities, their trophic structure as well as their use of basal resources in mountain scree are little studied despite the fact that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The third most numerous oribatid mite in the study -Carabodes subarcticus -was also found in such microhabitats as soil (e.g., Kagainis et al 2010Kagainis et al , 2015Hågvar et al 2014), touchwood, moss-covered branches (Żbikowska-Zdun et al 2006) and bark of deadwood (Bluhm et al 2015). The next species in terms of numbers was Oribatella calcarata which is ascribed to various trophic levels (Nae et al 2021) and is known to inhabit such habitats as soil, cave mud, dead wood, leaves, and guano in the caves (Niedbała and Rohloff 1971;Maślak and Barczyk 2011).…”
Section: Species Ecologymentioning
confidence: 74%
See 1 more Smart Citation
“…The third most numerous oribatid mite in the study -Carabodes subarcticus -was also found in such microhabitats as soil (e.g., Kagainis et al 2010Kagainis et al , 2015Hågvar et al 2014), touchwood, moss-covered branches (Żbikowska-Zdun et al 2006) and bark of deadwood (Bluhm et al 2015). The next species in terms of numbers was Oribatella calcarata which is ascribed to various trophic levels (Nae et al 2021) and is known to inhabit such habitats as soil, cave mud, dead wood, leaves, and guano in the caves (Niedbała and Rohloff 1971;Maślak and Barczyk 2011).…”
Section: Species Ecologymentioning
confidence: 74%
“…This mycophagous species (Schneider et al 2005) is known from sporocarps (Hågvar et al 2014) and is also found in litter, which combines patchily distributed microhabitats that are inhabited by specialised species groups (Wehner et al 2016) with soil (e.g., Błoszyk and Olszanowski 1997;Seniczak et al 2006;Manu and Honciuc 2010), nests of Formica rufa ants (Sell 1990), cave mud, deadwood, leaves and guano (Maślak and Barczyk 2011). In addition, Carabodes areolatus -a species categorised as secondary decomposer (Nae et al 2021) -was found not only in polypores (Hågvar and Steen 2013;Hågvar et al 2014;Maraun et al 2014), but also in soil (Błoszyk and Olszanowski 1997;Lebedeva and Krivolutsky 2003), feathers of hooded crow (Corvus corone cornix), magpie (Pica pica) and rook (Corvus frugilegus) (Krivolutsky and Lebedeva 2004). The third most numerous oribatid mite in the study -Carabodes subarcticus -was also found in such microhabitats as soil (e.g., Kagainis et al 2010Kagainis et al , 2015Hågvar et al 2014), touchwood, moss-covered branches (Żbikowska-Zdun et al 2006) and bark of deadwood (Bluhm et al 2015).…”
Section: Species Ecologymentioning
confidence: 99%
“…Although most of the OTUs were not identified to species level, feeding preferences of species are mostly the same within each family ( Krantz & Walter, 2009 ; Potapov et al, 2016 ). Soil mites were divided in predators (including omnivorous) and no predators (including primary and secondary decomposers) ( Schneider et al, 2004 ; Krantz & Walter, 2009 ; Maraun et al, 2011 ; Fischer, Meyer & Maraun, 2014 ; Maaß et al, 2015 ; Schaefer & Caruso, 2019 ; Nae et al, 2021 ). We preferred using such broader categorization since the trophic guilds of many species are still unknown.…”
Section: Methodsmentioning
confidence: 99%
“…MSSs are inhabited by species with different ecological requirements (epigean, edaphobionts, and troglobionts, among others) (e.g., Nitzu et al, 2014;Jiménez-Valverde et al, 2015;Mammola et al, 2016). Recently, new and rarely captured species have been frequently discovered in MSSs (e.g., Baquero et al, 2017;Gilgado et al, 2017;Ledesma et al, 2019;Jordana et al, 2020), allowing for a deeper understanding of the ecology of soil and subsoil habitats (Rendoš et al, 2012(Rendoš et al, , 2016Nitzu et al, 2014;Nae & Băncilă, 2017;Ledesma et al, 2020;Nae et al, 2021). MSS-research began in the Pyrenees (Juberthie et al, 1980(Juberthie et al, , 1981 and has been largely conducted in Europe (Mammola et al, 2016).…”
Section: Introductionmentioning
confidence: 99%